The Study of Economic Activity of Russian Corporations in Modern Economy - Golovanova, Natalia B.; Basyuk, Anait S.; Taranova, Irina V.; Kramarenko, Elena R.; Goloshchapova, Ludmila V. (International Journal of Economics and Financial Issues, 2016)
The article discusses the results of the conducted in Russia’s economic reforms, the terms “company”, “corporate governance” of their use in the media and in literature, as well as the formation of the idea of the control system adopted by the Corporation, as one of the ways of good governance and the withdrawal of Russian companies out of the crisis. The most urgent tasks in the practical management of corporate property can now be considered: clarifying the structure and composition of corporate ownership, the formalization of the goals, objectives and principles of its functioning, the definition of criteria for management efficiency, which, in turn, require search and study methodological approaches to solving specific economic tasks - evaluation of individual objects of corporate ownership and to determine effective areas of structural development. According to the authors, only the use of complex techniques from different sections of the economy can give the desired economic effect and solve the pressing problem of increasing the effectiveness of the management of corporate property in Russia. In this regard, the work deals with general principles of good governance and analyzed their application for enterprise property management purposes. Keywords: modern economy, Russia, corporate economic governance JEL Classifications: D23, G30, O16